Epidemiological characteristics of acute symptomatic hepatitis A in Al Alwyia pediatric teaching hospital during 2013 - Raham, Tareef F.; Abood **, Assad M. (AL-Kindy College Medical Journal, 2015)
ABSTRACTBackground: Concerns about hepatitis A infections is increasing worldwide specially after improving economic and sanitary conditions in many countries making older age groups who escape infection on early life vulnerable to infection.Objectives: The objectives were to estimate the frequency of hepatitis A among children consulting Al Alwyia pediatric Teaching Hospital during the year 2013 and to study some demographic characteristics of the disease.Methods: This cross - sectional hospital -based study wasconducted during 2013-2014 and include pediatric patients(43525 patients) who consult Al Alwyia pediatric hospitalduring that time. The outcome is total IgM antibodies tohepatitis A virus detected using Enzyme Linked FluorescentAssay (ELFA) the test is performed on 380 clinicallysuspected cases. The age distribution of the susceptiblepopulation is estimated using a simple catalytic model.Results: The age groups (1-4 and 5-–9) constitute 43.6% and 42 % of sero-positive cases respectively with a P valueof 0.001. The incidence is more among males (56%). Incidence is more during June and July 40 %and 15.6% respectively with a p value of 0.001. 1.2% needed causality or ward admissions.Conclusions: High incidence in school age group might indicate the transition to older age groups and vaccinations should be considered at near future.